Knee Strength Outcomes in Adolescents by Age and Sex During Late-Stage Rehabilitation After Anterior Cruciate Ligament Reconstruction. Issue 5 (31st May 2022) - Roman, Dylan P.; Ness, Brandon M.; Giampetruzzi, Nicholas; Cleland, Joshua A.; Weaver, Adam
Background: The incidence of anterior cruciate ligament (ACL) injuries have been consistently increasing in adolescents, with those who return to competitive sport having up to a 32% risk of a secondary ACL injury. There is limited evidence regarding knee strength outcomes in young adolescents following ACL reconstruction during late-stage rehabilitation when compared to older patient groups. Purpose: The purpose of this study was to 1) establish normative knee strength values according to age group in adolescent female and male patients during late-stage rehabilitation following ACLR and 2) determine whether strength differences exist between age groups. Methods: A retrospective review of adolescent patients who underwent primary ACL reconstruction was performed. Patients completed a standardized isokinetic (60°/sec) knee extension and flexion strength assessment during late-stage rehabilitation. Peak torque was normalized to the patient's body mass (Nm/kg) and used to calculate Limb Symmetry Index (LSI). Analyses were conducted separately for female and male cohorts and grouped by early (11-14 years) and middle (15-17 years) adolescence. An independent samples t-test examined strength differences between age groups. Results: 130 females (age=15.4 ± 1.4 years; days since surgery=239.0 ± 84.4) and 112 males (age=15.4 ± 1.5 years; days since surgery= 232.6 ± 91.2) were included. Normalized knee extension peak torque on the involved limb was reported for female (1.5 Nm/kg) and male (1.8 Nm/kg) cohorts. Differences between age groups in knee extension peak torque were found on the surgical and nonsurgical limbs in female (p = 0.02 – 0.05) and male (p<0.001 – 0.002) cohorts. No differences were found between age groups for either cohort when normalized to body mass (p = 0.30 – 0.89). Post hoc power analyses revealed 67% statistical power in the female cohort and 97% in the male cohort with an alpha level set to 0.05 based on the observed effect size for the differences in isokinetic knee extension/flexion peak torque between age groups. Conclusion: Early adolescents produced less knee extension and flexion peak torque compared to middle adolescents after ACLR, but no differences were found between age groups when normalized to body mass for female or male cohorts. Normalized knee extension strength in young adolescents may differ from older patients and should be considered in the rehabilitation process. TABLE 1: Patient Demographics - Females TABLE 2: Patient Demographics - Males TABLE 3: Strength Outcomes by Age Group during Late-Stage Rehabilitation (Females) TABLE 4: Strength Outcomes by Age Group during Late-Stage Rehabilitation (Males)